Ultrastructural Biomarkers in Symbiotic Algae Reflect the Availability of Dissolved Inorganic Nutrients and Particulate Food to the Reef Coral Holobiont - Rosset, Sabrina; D'Angelo, Cecilia; Wiedenmann, Jörg (Frontiers in Marine Science, 2015)
Reef building corals associated with symbiotic algae (zooxanthellae) can access environmental nutrients from different sources, most significantly via the uptake of dissolved inorganic nutrients by the algal symbiont and heterotrophic feeding of the coral host. Climate change is expected to alter the nutrient environment in coral reefs with the potential to benefit or disturb coral reef resilience. At present, the relative importance of the two major nutrient sources is not well understood, making predictions of the responses of corals to changes in their nutrient environment difficult. Therefore, we have examined the long-term effects of the availability of different concentrations of dissolved inorganic nutrients and of nutrients in particulate organic form on the model coral Euphyllia paradivisa. Coral and algal biomass showed a significantly stronger increase in response to elevated levels of dissolved inorganic nutrients as compared to the supply with particulate food. Also, changes in the zooxanthellae ultrastructure, determined by transmission electron microscopy (TEM), were mostly driven by the availability of dissolved inorganic nutrients under the present experimental conditions. The larger size of symbiont cells, their increased accumulation of lipid bodies, a higher number of starch granules and the fragmentation of their accumulation body could be established as reliable biomarkers of low availability of dissolved inorganic nutrients to the coral holobiont.